2020
DOI: 10.3390/insects11060374
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Ectopic Overexpression of Broad Complex (BrC-Z2) in the Silk Gland Inhibits the Expression of Silk Fibroin Genes of Bombyx mori

Abstract: Bombyx mori silk protein genes are strictly turned on and off in different developmental stages under the hormone periodically change. The broad complex (BrC) is a transcription factor mediating 20-hydroxyecdysone action, which plays important roles during metamorphosis. Here, we observed that two isoforms of BmBrC (BmBrC-Z2 and BmBrC-Z4) exhibited contrasting expression patterns with fibroin genes (FibH, FibL and P25) in the posterior silk gland (PSG), suggesting that BmBrC may negatively regulate fibroin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our data suggest that the MARs found in the coding regions of Br-c may be involved in the down-regulation of the broad-complex which in turn increase the FIBH expression. This is consistent with studies that showed ectopic expression of Br-c Z2 inhibited FIBH expression (67).…”
Section: Dynamic Attachment Of Fibh and Br-c Regions With The Nuclear...supporting
confidence: 92%
See 1 more Smart Citation
“…Our data suggest that the MARs found in the coding regions of Br-c may be involved in the down-regulation of the broad-complex which in turn increase the FIBH expression. This is consistent with studies that showed ectopic expression of Br-c Z2 inhibited FIBH expression (67).…”
Section: Dynamic Attachment Of Fibh and Br-c Regions With The Nuclear...supporting
confidence: 92%
“…Previous work from our lab showed that the broad-complex negatively regulates broin gene expression (66).This was further supported by a study by a recent study that showed that the overexpression of BmBr-c Z2 in the transgenic lines of B. mori led to decline in the FIBH, Fib-l and P25 silk proteins. This mechanism was shown to be connected with the juvenile hormone pathway which is linked to the expression of its transcription factors, Bmdimm and BmKr-h1 (67). The expression of Bmdimm was shown to positively regulate FIBH which correlates with the effect of Br-c expression on the regulation of FIBH expression (68).…”
Section: Dynamic Attachment Of Fibh and Br-c Regions With The Nuclear...mentioning
confidence: 95%
“…Generally, silkworm development is affected by changes in the prothoracic gland, corpus allatum, fat body, hemolymph, and other organs; however, abnormal silk protein synthesis and silk gland development did not affect the development of larvae (Cong et al, 2020; Hu et al, 2019; Ma et al, 2014). Therefore, we speculate that Bmdimm may also function in other organs.…”
Section: Resultsmentioning
confidence: 99%
“…mori ‐derived salivary gland‐expressed bHLH (Bmsage) (Zhao et al, 2014), B . mori ‐derived dimmed (Bmdimm) (Zhao et al, 2015); negative regulatory factors, fibroin modulator‐binding protein 1 (FMBP‐1) (Liu et al, 2019; Takiya et al, 1997), fushi tarazu‐transcription factor 1 (Ftz‐F1) (Zhou, Zha, Shi, Zhao, et al, 2016), multiprotein bridging factor 2 (MBF2) (Zhou, Zha, Shi, Wei, et al, 2016), broad complex isoform 2 (Brc‐Z2) (Cong et al, 2020); and silk gland factor‐4 (SGF4) (Hui et al, 1990) and fem‐3 binding factor (FBF‐A1) (Hui et al, 1990). Most transcription factors, including the Bmdimm gene, are involved in the regulation of FibH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation